National comparisons of early career researchers' scholarly communication attitudes and behaviours. Issue 4 (4th June 2020) - Jamali, Hamid R.; Nicholas, David; Herman, Eti; Boukacem‐Zeghmouri, Cherifa; Abrizah, Abdullah; Rodríguez‐Bravo, Blanca; Xu, Jie; Świgon', Marzena; Polezhaeva, Tatiana; Watkinson, Anthony
Abstract : The paper compares the scholarly communication attitudes and practices of early career researchers (ECRs) in eight countries concerning discovery, reading, publishing, authorship, open access, and social media. The data are taken from the most recent investigation in the 4‐year‐long Harbingers project. A survey was undertaken to establish whether the scholarly communication behaviours of the new wave of researchers are uniform, progressing, or changing in the same overall direction or whether they are impacted significantly by national and cultural differences. A multilingual questionnaire hosted on SurveyMonkey was distributed in 2019 via social media networks of researchers, academic publishers, and key ECR platforms in the UK, USA, France, China, Spain, Russia, Malaysia, and Poland. Over a thousand responses were obtained, and the main findings are that there is a significant degree of diversity in terms of scholarly communication attitudes and practices of ECRs from the various countries represented in the study, which cannot be solely explained by the different make‐up of the samples. China, Russia, France, and Malaysia were more likely to be different in respect to a scholarly activity, and responses from the UK and USA were relatively similar. Key points: ECRs from China, Russia, France, and Malaysia are more likely to hold different (although moderate) views in respect to a scholarly activity. ECRs from the UK and USA are similar in many respects, including being positive towards open science and relying less on external factors (impact factor or number of download) for their decision to read a paper. French ECRs appear not to want to do, abide, or follow anything novel or innovative and are very critical of scholarly developments. Spanish ECRs are innovative and more positive about publishing open access (OA), while Chinese ECRs are somewhat conservative as they are less likely to publish in OA Chinese ECRs are the highest users of social media for testing and conducting research but least likely to use it to share their reputations or build reputations.